Differences in clinical outcomes of COVID-19 among vaccinated and unvaccinated kidney transplant recipients. Issue 24 (26th May 2022) - Demir, Erol; Dheir, Hamad; Safak, Seda; Serra Artan, Ayse; Sipahi, Savas; Turkmen, Aydin
Abstract: Introduction: The remarkable efficacy and effectiveness of COVID-19 vaccines have been described in healthy individuals, but kidney transplant recipients have been excluded from these studies. Therefore, real-world evidence of these vaccines can guide clinicians in predicting complications in kidney transplant recipients and how many doses of vaccines are protective. In this study, we aimed to investigate the impact of the COVID-19 vaccines on kidney transplant recipients with SARS-CoV-2 infection. Material and method: This matched case-control study included vaccinated kidney transplant recipients with COVID-19 from two centers between 1 May and 1 October 2021. All patients in the vaccinated group received a minimum of two doses of the vaccine and were diagnosed with COVID-19 at least one month after the last dose. Each vaccinated patient was matched with an unvaccinated kidney transplant recipient diagnosed with COVID. The endpoints were all-cause mortality, hospitalization, intensive care unit admission, acute kidney injury, cytokine storm, and acute respiratory distress syndrome. Results: The median age of vaccinated seventy-two participants was 45 years, and 41 of the participants were men in the vaccinated group. Four patients in the vaccinated group and nine patients in the control group died during follow-up (p = 0.247). Seventeen patients in the vaccinated group, thirty-four participants in the control group were hospitalized (p = 0.004); five vaccinated patients and ten unvaccinated patients were followed-up in the ICU during follow-up (p = 0.168). Thirteen of the vaccinated and twelve unvaccinated patients developed acute kidney injury (p = 0.16). The occurrence of cytokine storm (n = 4 vs. n = 11; p = 0.061) and acute respiratory distress syndrome (n = 5 vs. n = 10; p = 0.168) was higher in the patient group compared to the control group. Conclusion: COVID-19 remains a fatal disease despite advancing treatment modalities and preventive strategies. COVID-19 vaccines can't prevent death in all kidney transplant recipients, but they decrease hospitalization rate and duration in most patients.